2019
DOI: 10.1186/s12938-019-0667-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac monitoring of dogs via smartphone mechanocardiography: a feasibility study

Abstract: Background In the context of monitoring dogs, usually, accelerometers have been used to measure the dog’s movement activity. Here, we study another application of the accelerometers (and gyroscopes)—seismocardiography (SCG) and gyrocardiography (GCG)—to monitor the dog’s heart. Together, 3-axis SCG and 3-axis GCG constitute of 6-axis mechanocardiography (MCG), which is inbuilt to most modern smartphones. Thus, the objective of this study is to assess the feasibility of using a smartphone-only solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Heartbeat detection is based on the fact of quasi-periodic occurrence of waves associated with heartbeats [ 8 ]. The wave which indicates the heartbeat in seismocardiograms and gyrocardiograms is the aortic valve opening (AO) wave [ 28 , 30 ] also known as the wave in GCG signal morphology [ 8 ]. The AO wave occurs within 100 ms after the occurrence R wave in ECG signal [ 8 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Heartbeat detection is based on the fact of quasi-periodic occurrence of waves associated with heartbeats [ 8 ]. The wave which indicates the heartbeat in seismocardiograms and gyrocardiograms is the aortic valve opening (AO) wave [ 28 , 30 ] also known as the wave in GCG signal morphology [ 8 ]. The AO wave occurs within 100 ms after the occurrence R wave in ECG signal [ 8 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…New topics on gyrocardiography described in 2019 include performing cardiac monitoring of dogs via smarthphones [ 71 ], fetal heart rate (FHR) monitoring [ 72 ], investigating the influence of respiratory volume on the SCG and GCG waveforms [ 73 ] and evaluating the motion-based heart rate measurement [ 74 ]. Yang et al conducted the study on FHR estimation based on fetal cardiotocography sensor and the reported positive percent agreement (the equivalent of sensitivity/TPR when the reference is uncertain [ 75 ]) was 75.52% from GCG [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GCG along with the SCG and BCG constitute the mechanocardiography (MCG) or vibrational cardiography (VCG). The first term was proposed by [ 24 , 49 , 55 , 58 , 60 , 64 , 65 , 71 , 73 , 77 , 88 ] and the second term was proposed by [ 9 , 73 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations